ARCHITECTONIC REGIONALISME DALAM ARSITEKTUR OSING - Dharmatanna, Stephanus Wirawan (ALUR :Jurnal Arsitektur, 2023)
Architectonic regionalism is an approach that seeks to incorporate regional identity into contemporary architecture. This study focuses on the application of architectonic regionalism in Osing architecture, a traditional architecture style found in the Banyuwangi region of East Java, Indonesia. Using a qualitative research method with a descriptive approach, the study analyzes three case studies of modern buildings - Hotel Sahid Osing, Blimbingsari Airport, and Polytechnic Banyuwangi Hall - that showcase reinterpretation, modification, and innovation of local architectural elements. The study finds that the architectonic regionalism approach in Osing architecture prioritizes the use of traditional materials such as wood from local mangrove forests, and construction techniques that are adapted from local practices. The topography of the site is also considered in the design process, with the buildings being responsive to the natural landscape. Moreover, local cultural values and symbolism are incorporated into the architecture, reflecting the unique identity of the Osing community. The findings of this research highlight the importance of preserving and promoting regional architectural traditions in the context of modern architecture. The reinterpretation, modification, and innovation of local architectural elements in contemporary buildings can contribute to the sustainability and cultural preservation of the region. Furthermore, the architectonic regionalism approach in Osing architecture serves as a case study for understanding how regional identity can be manifested in modern architectural design, and its implications for sustainable development and cultural heritage preservation.